2013
DOI: 10.2119/molmed.2013.00049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Microsatellite Instability and KRAS and BRAF Mutations on Lymph Node Harvest in Stage I–III Colon Cancers

Abstract: Lymph node (LN) harvest is influenced by several factors, including tumor genetics. Microsatellite instability (MSI) is associated with improved node harvest, but the association to other genetic factors is largely unknown. Research methods included a prospective series of stage I-III colon cancer patients undergoing ex vivo sentinel-node sampling. The presence of MSI, KRAS mutations in codons 12 and 13, and BRAF V600E mutations was analyzed. Uni-and multivariate regression models for node sampling were adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…The association between microsatellite instability and lymph node yield has also been explored. Adequate lymph node harvest was more likely seen in tumours with microsatellite instability, with an odds ratio of 2.3 to 2.5 [28,29]. While tumours with microsatellite instability were known to be associated with a good prognosis, whether this is the answer as to why patients with a greater lymph node yield had better survival remains to be elucidated [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…The association between microsatellite instability and lymph node yield has also been explored. Adequate lymph node harvest was more likely seen in tumours with microsatellite instability, with an odds ratio of 2.3 to 2.5 [28,29]. While tumours with microsatellite instability were known to be associated with a good prognosis, whether this is the answer as to why patients with a greater lymph node yield had better survival remains to be elucidated [30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have attempted to assess LNC variability and have demonstrated a variety of factors, including the patient's anatomy, tumor biology, experience of the gross examiner, and use of fat-clearing solutions. 6,[8][9][10][11][12] Although many of these studies also identify the pathologist as a significant source of variation, this has not been uniformly true. 13 By far, the least investigated aspect of LNC is the actual enumeration process of the pathologist during microscopic review; however, this is the time at which the LNC is determined.…”
Section: High Variability In Lymph Node Counts Among An Internationalmentioning
confidence: 99%
“…KRAS is known as an early mutated event in CRC and is found in approximately 15% of patients with advanced adenomas and in 35% to 45% of patients with primary CRC (TNM stages I-III). 8,9 The frequency of KRAS mutations in patients with a CRLM corresponds well, but not perfectly, with the status of the primary tumor. Studies have reported the variably of KRAS testing in the primary tumor, metastasis, or both, with some mutations noted on formalin-fixed and others on fresh frozen tissue.…”
mentioning
confidence: 98%
“…It is interesting to note that patients with KRAS wild‐type status respond best to anti‐EGFR treatment. KRAS is known as an early mutated event in CRC and is found in approximately 15% of patients with advanced adenomas and in 35% to 45% of patients with primary CRC (TNM stages I‐III) . The frequency of KRAS mutations in patients with a CRLM corresponds well, but not perfectly, with the status of the primary tumor.…”
mentioning
confidence: 99%
See 1 more Smart Citation